Interaksi Antara Ekstrak Clitoria ternatea L Dan Antibiotik Pada Aktivitas Antibakteri Terhadap Staphylococcus aureus - Nabila Wanda, Yumna Hanum; Rahma Putri, Citra Destya; Risandiansyah, Rio (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
Antibiotic combination is a strategy to enhance antibacterial effectiveness by acting on different cellular targets. The utilization of natural ingredients as adjuvants also has the potential to improve antimicrobial responses. Butterfly pea (Clitoria ternatea L.) is known to contain antibacterial compounds that can potentiate antibiotic activity. Research regarding the interaction of Clitoria ternatea extracts with antibiotics against Staphylococcus aureus remains limited; therefore, this study aims to evaluate the interaction patterns of these combinations. Clitoria ternatea L. simplicia was macerated using three solvents: ethanol, ethyl acetate, and n-hexane. Antibacterial testing was conducted based on the Zone of Inhibition (ZOI) using the Ameri-Ziaei Double Antibiotic Synergism Test (AZDAST) method, which is suitable as an initial screening method for antimicrobial interactions. Extracts were tested at a concentration of 50% (500,000 ppm), with the inoculum standardized to 0.5 McFarland, and each treatment was replicated 3×2 times. Data were analyzed using One-way ANOVA or non-parametric tests (Kruskal-Wallis) depending on the data distribution, followed by appropriate post hoc tests (Tukey, Games-Howell, or Mann-Whitney). The significance level was set at p < 0,05, and the type of interaction was determined based on AZDAST interpretation criteria (synergistic, additive, antagonistic, or not distinguishable). The results showed that the combination of ethanol extract and amoxicillin produced an additive effect (55.06 ± 1.68 mm), The combination of ethyl acetate extract with amoxicillin (52.38 ± 2.60 mm). n-hexane extract with amoxicillin (52.60 ± 3.99 mm), and all extract combinations with tetracycline (37.76-42.70 mm) yielded results that were not distinguishable compared to either single antibiotics or their double doses. It can be concluded that the combination of ethanol and ethyl acetate extracts with amoxicillin can enhance antibacterial activity compared to single treatments by providing an additive effect. Meanwhile, the combinations of ethanol and ethyl acetate extracts with tetracycline, as well as the combinations of n-hexane extract with both amoxicillin and tetracycline, showed no significant difference (not distinguishable).